Pengaruh High Performance Work Systems terhadap Community Participation Melalui Feeling Trusted dan Knowledge Sharing Behavior - Cindy Wilian Despita; Kartika Febri Yuliani; Justine Tanuwijaya (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to analyze the effect of high performance work systems on community participation through feeling trusted and knowledge sharing behavior. Data is collected from all employees of financial services industry companies in Indonesia. According to Hair et al., (2014) where the sample recommendation in the study is the number of indicators multiplied by at least 5 times (32 x 5 = 160 respondents), the researchers distributed questionnaires and took a sample of 160 people to represent the population. The data analysis method in this study uses descriptive statistics based on respondents' answers to analyze each variable, namely High Performance Work System, Feeling Trusted, Knowledge Sharing Behavior and Community Performance. The results showed that there was an effect of High Performance Work Systems on Feeling Trusted, a positive effect Feeling Trusted on Knowledge Sharing Behavior, positive influence of Knowledge Sharing Behavior on Community Participation, positive influence of High Performance Work Systems on Community Participation mediated by Knowledge Sharing Behavior, positive influence of Feeling Trusted on Community Participation mediated by Knowledge Sharing Behavior and no positive influence High Performance Work Systems on Knowledge Sharing Behavior.